Analysis of Documents Published in Scopus Database on Foreign Language Learning Through Mobile Learning: A Content Analysis (2017)
The purpose of this study is to determine the recent trends in foreign language learning through mobile learning. The study was conducted employing document analysis and related content analysis among the qualitative research methodology. Through the search conducted on Scopus database with the key words “mobile learning and foreign language learning”, the study is based on the analysis of the documents published between the years 2005 and 2017; their distribution took place by years, subject areas, document types, country/regions, and the affiliated universities of the authors. The varied findings revealed that the analysis of the studies published on Scopus database was important in terms of content for the significance of foreign language learning through mobile learning.